Barriers to the participation of women in community development process in rural Ghana: a regression analysis. Issue 4 (19th May 2022) - Gyan, Charles; Malik, Maya; Siddique, Aisha
ABSTRACT: Women across the world face a myriad of barriers in every sphere of their socio-economic life, negatively affecting their ability to utilise available societal resources to achieve their full potential. They are often relegated to the background when it comes to participation in community development and decision-making. The present study seeks to examine the relative strength of barriers to women's involvement in the community development processes in rural Ghana. A multistage sampling technique was used to recruit 210 women from three rural communities in Ghana. A questionnaire comprising a series of scales was used to collect the data. The study found that the most critical barriers faced by women in rural Ghana include the patriarchal norms of Ghanaian society, as well as behavioural, and idiosyncratic patterns associated with their socialisation. The study recommends the provision of opportunities to communities to be able to empower and encourage themselves to make the cultural shifts necessary to overcome and address the key barriers women face. Community development processes must incorporate meaningful participatory approaches geared towards greater equality, freedom, and advancement of local community members, especially women.